2014
DOI: 10.19030/iber.v13i2.8447
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Hyperbolic Distributions And Value-At-Risk Estimation For The South African Mining Index

Abstract: South Africa is a cornucopia of mineral riches and the performance of its mining industry has significant impacts on the economy. Hence, an accurate distributional assumption of the underlying mining index returns is imperative for the forecasting and understanding of the financial market. In this paper, we propose three subclasses of the generalized hyperbolic distributions as appropriate models for the Johannesburg Stock Exchange (JSE) Mining Index returns. These models are shown to outperform the traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Further work may include comparative analyses with other heavy-tail distributions, that are suitable for the depiction of financial returns, and incorporation of GPD in the framework of the well-known GARCH-based VaR models. For example, comparisons may be drawn with the generalised logistic distribution (Tolikas & Brown, 2006) and the class of generalised hyperbolic distributions (Huang et al, 2014), with the inclusion of backtesting results on the VaR and ES estimates. R and EViews were used in this paper to produce figures and results from various tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further work may include comparative analyses with other heavy-tail distributions, that are suitable for the depiction of financial returns, and incorporation of GPD in the framework of the well-known GARCH-based VaR models. For example, comparisons may be drawn with the generalised logistic distribution (Tolikas & Brown, 2006) and the class of generalised hyperbolic distributions (Huang et al, 2014), with the inclusion of backtesting results on the VaR and ES estimates. R and EViews were used in this paper to produce figures and results from various tests.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to VaR, ES measures the riskiness of an instrument by considering both the size and likelihood of losses above a particular threshold (Basel, 2012). ES gives the expected size of return that exceeds VaR, i.e., for a probability level p, (16) And, equivalently, (17) where the second term above represent the mean of the excess distribution (treating as the threshold). Proceeding as before, if the threshold is sufficiently large then is a GPD, i.e.,…”
Section: Esmentioning
confidence: 99%
“…Through various perspectives, Fajardo, Farias and Ornelas recommended the use of the GH family distribution estimating by the maximum log likelihood method. Huang, et al (2014) applied the generalized hyperbolic distributions for VaR estimation for the South African mining index. Through the comparison of three subclasses of the generalized hyperbolic distributions using the Akaike information criterion (AIC), the Bayesian information criterion (BIC) and log-likelihoods, Huang, et al found the generalized hyperbolic (GH) skew Student's t distribution as the most robust model for the South African mining index returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Modelling these innovations has received a great interest among practitioners and parametric estimation of their distribution is conducted with distributions such as the Generalized Hyperbolic (GHYP) [6] and Skewed Exponential Power (SEPD) [7]- [8] distributions. Recently, Polynomial-Normal [9] and Polynomial-t-Student distributions [10] were used to fit the innovation of GARCH models for financial series.…”
Section: Introductionmentioning
confidence: 99%